Rad52 SUMOylation affects the efficiency of the DNA repair - Altmannova, Veronika; Eckert-Boulet, Nadine; Arneric, Milica; Kolesar, Peter; Chaloupkova, Radka; Damborsky, Jiri; Sung, Patrick; Zhao, Xiaolan; Lisby, Michael; Krejci, Lumir (Nucleic acids research, 2010)
Homologous recombination (HR) plays a vital role in DNA metabolic processes including meiosis, DNA repair, DNA replication and rDNA homeostasis. HR defects can lead to pathological outcomes, including genetic diseases and cancer. Recent studies suggest that the post-translational modification by the small ubiquitin-like modifier (SUMO) protein plays an important role in mitotic and meiotic recombination. However, the precise role of SUMOylation during recombination is still unclear. Here, we characterize the effect of SUMOylation on the biochemical properties of the Saccharomyces cerevisiae recombination mediator protein Rad52. Interestingly, Rad52 SUMOylation is enhanced by single-stranded DNA, and we show that SUMOylation of Rad52 also inhibits its DNA binding and annealing activities. The biochemical effects of SUMO modification in vitro are accompanied by a shorter duration of spontaneous Rad52 foci in vivo and a shift in spontaneous mitotic recombination from single-strand annealing to gene conversion events in the SUMO-deficient Rad52 mutants. Taken together, our results highlight the importance of Rad52 SUMOylation as part of a 'quality control' mechanism regulating the efficiency of recombination and DNA repair.
Keywords: rekombinace genetická; Rad51 Recombinase; Rad52 DNA Repair and Recombination Protein; lysin; SUMO-1 Protein; Recombination, Genetic; Lysine; Replication Protein A; oprava DNA; Saccharomyces cerevisiae - proteiny; rekombinasa Rad51; DNA, Single-Stranded; protein SUMO-1; jednovláknová DNA; DNA opravný a rekombinační protein Rad52; DNA Repair; Saccharomyces cerevisiae Proteins; replikační protein A; terciární struktura proteinů; Protein Structure, Tertiary